PENGARUH BELANJA MODAL DAN PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN DI PROVINSI SULAWESI UTARA - Sompotan, Graciella Brigita; Rori, George A.; Malau, Natalia A. (Program Studi Ilmu Ekonomi, 2025)
Abstract: This research aims to determine the effect of capital expenditure and economic growth on poverty in North Sulawesi. This research took North Sulawesi Province as the research location. In 2003-2022, poverty rates experienced fluctuations influenced by factors such as capital expenditure strategies carried out by local governments that were not appropriate to problems and economic development programs that had not yet spread to every community, including the poor. This type of research is a quantitative approach. Data collection techniques with documentation, data collection tools are in the form of documentation obtained from the Central Statistics Agency (BPS). The method used in this research is multiple linear regression with the 2003-2022 time series using the Eviews Ordinary Least Square (OLS) analysis tool. 8. Based on the results of this research, it can be concluded that Capital Expenditures have a negative and significant effect on Poverty in North Sulawesi Province. Economic Growth does not have a significant effect on Poverty in North Sulawesi Province. Keywords: Poverty, Capital Expenditure, Economic Growth